INTRODUCING A âBALANCEâ IN THE BSC THROUGH BEAUTY AND LOVE - Kamayanti, Ari (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Celebrating the seventeenth anniversary of the Balanced Score Card (BSC) since it was born in 1992, this paper revisits its concept as one of the landmarks in performance measurement. The BSC turns out to be ânot so balancedâ since it lacks certain beauty and love. It hinges on accountability for certain interests when measuring performance, negating or putting other interests as minority. Thus, it fits perfectly with the aim of management accounting that puts managers and customers as priorities. The imbalances comes from secularism and overemphasis in rationalism. Sustainability that becomes the current issue nowadays would not be supported by such performance measurement. In order to insert this balance, a methodology by taking a methapor of nurturing mother is applied in this research that encompasses gentle beauty and subtle love. Gentle beauty refers to a complete harmony of beauty : irrational and the rational; this means introducing those that have been left out in the name of rationality such as religions and spiritualism. Subtle love refers to love towards God that is expressed subtly without lust to overpower. The result is a more balanced set of performance measurements that are filled with beauty and love, insyaAllah.